EVALUATION OF RICE GENOTYPES AGAINST SHEATH BLIGHT USING BASIC RESISTANCE COMPONENTS FOR RESISTANCE IDENTIFICATION - SURESH MADUGULA*, PARIMAL K SINHA; RAJU M.R.B (The Journal of Research ANGRAU, 2023)
Under the current climate change scenario, sheath blight caused by Rhizoctonia solani, a necrotrophic pathogen, is becoming a serious threat, causing significant yield losses in paddy, especially in the coastal ecosystem of Andhra Pradesh state. Resistance evaluation in popular rice cultivars taken up during 2020-21 season at Regional Agricultural Research Station, Maruteru (field studies) and Division of Plant Pathology, ICAR-IARI, New Delhi (lab studies) for identification of resistance sources for further breeding programmes using resistance components revealed that using single phenotypic component based arbitrary scale may not reveal the true varietal nature with respect to disease resistance and needs to consider the host-pathogen population dynamics. Among the three basic resistance components studied, rate of infection (RRBR) and incubation period (RRIP) found to have greater bearing on sheath blight resistance, whereas, lesion length (RRLL) found to be a less potential indicator for quantifying the resistance levels in the rice cultivars for sheath blight.